Effect of Probiotics on Infantile Colic Using the Quadratic Inference Functions - Maryam Tatari; jamshid Yazdani-charati; Hassan Karami; Hamed Rouhanizadeh (Iranian Journal of Neonatology, 2017)
Background: Infantile colic is defined as episodes of extreme and excessive crying due to unknown causes. Various results have been reported regarding the management of colic with probiotics in terms of effectiveness, with no side effects or health risks in the infants. The present study aimed to evaluate the effect of probiotics on the infants with colic using the quadratic inference functions (QIF).Methods: This single-blind, randomized, clinical trial was conducted on 98 infants admitted to the pediatric gastroenterology clinic of Bu Ali Sina Hospital in Sari, Iran. The neonates were diagnosed with infantile colic by a pediatric gastroenterologist. Patients were randomly divided into two groups (49 subjects per each). In the control group, the infants received placebo, and in the case group, the neonates were administrated with BioGaia probiotic oral drops for 21 days. The QIF method was fitted to analyze the influential factors in the improvement of infantile colic.Results: According to the QIF results in data analysis, mean duration of crying had a significant difference between the infants in the case and control groups (P